Ketuhanan dan Keadaban Sosial : Membangun Nilai-Nilai Moral di Tengah Krisis Sosial - Anita Mariana Parulian (Badan Penerbit STIEPARI Press, 2024)
The current social crisis gripping Indonesian society reflects the degradation of moral and ethical values in public life. Phenomena such as intolerance, social violence, community disintegration, declining empathy, and weakening solidarity indicate a rift in the value system long upheld by the Indonesian people. This situation raises deep concern, as the noble values embodied in Pancasila are slowly being neglected in everyday life. This paper aims to examine in more depth the role of the values of Divinity and Social Civility as the primary foundation for rebuilding public morality amidst the current social crisis. The method used is descriptive-qualitative, drawing on literature review, normative analysis, and socio-cultural reflection on the values of Pancasila. The results of this study indicate that Belief in the One and Only God is not only spiritual but also demands ethical and social responsibility from every individual in life within society, the nation, and the state. These values foster an awareness of the importance of integrity, honesty, and respect for others. Meanwhile, social civility reflects the concrete implementation of just and civilized human values, which should be realized through an attitude of tolerance, respect for differences, social justice, and the practice of mutual cooperation. By consistently instilling these values through formal and non-formal education, the role of the family as the primary character-building environment, and public policies oriented toward moral strengthening, it is hoped that society will be able to rebuild collective moral awareness. Ultimately, the revitalization of divine values and social civility is key to creating a harmonious, inclusive, and just social life.